Application of HEC-HMS Model in Flood Simulation of Qingshan River Basin - PENG Chujie (Renmin Zhujiang)
It is more and more important to realize the fast simulation of flood process in the early warning of mountain flood disaster in small and medium river basins.This paper builds a distributed hydrological model for Qingshan River Basin by combining HEC-HMS model with GIS technology,extracts the characteristics of river system and conducts gridding on small basin based on DEM data,calculates the surface runoff by initial and constant loss method and Snyder unit hydrograph method,simulates the process of base flow recession through nonlinear boussinesq method,conducts the channel routing by Muskingum method,calibrates the parameters with the past 5 measured flood data,as well as verifies the prediction results by 13 floods.The simulation results show that during the verification period,the errors of peak discharge are all within 20%,the time difference for peaks is less than 3 h,the certainty coefficient is less than 0.7 for only 2 floods,and above 0.7 for others.The results show that with high accuracy and stability,the HEC-HMS model for flood simulation in this river basin conforms to the requirements of the flood forecast,which is of great application value for the exploration of small basin flood simulation and analysis.